Antimicrobial, anticancer, and antioxidant compounds from Premna resinosa growing in Saudi Arabia. (1st January 2017) - Albadawi, Dina A.; Mothana, Ramzi A.; Khaled, Jamal M.; Ashour, Abdelkhader E.; Kumar, Ashok; Ahmad, Sheikh F.; Al-Said, Mansour S.; Al-Rehaily, Adnan J.; Almusayeib, Nawal M.
Abstract: Context: Premna resinosa (Hochst.) Schauer (Lamiaceae) is used in many places to treat bronchitis, respiratory illness and convulsions of the rib cage. Objective: This study evaluates the anticancer, antimicrobial and antioxidant activities of P. resinosa, and isolates some responsible constituents. Materials and methods: The methanol extract of P. resinosa aerial parts and its fractions ( n -hexane, dichloromethane, ethyl acetate and n -butanol) were tested. Antimicrobial activity was tested using microdilution method against three Gram-positive and four Gram-negative bacteria. The tested concentrations ranged from 4000 to 7.8 μg/mL and MIC values were determined after 24 h incubation. Anticancer activity was evaluated against three human cancer cell lines (Daoy, HepG2 and SK-MEL28) using MTT assay. Antioxidant activity was investigated by DPPH scavenging method and β-carotene-linoleic acid assay. Results: The greatest antimicrobial activity was exhibited by n -hexane fraction (MIC 10 μg/mL) against Staphylococcus aureus, Enterococcus faecalis, and Shigella flexneri . The n -hexane fraction induced the greatest cytotoxic activity against Daoy, HepG2, and SK-MEL28 cell lines with IC50 values of 9.0, 8.5 and 13.2, respectively. Moreover, the dichloromethane and ethyl acetate fractions showed the highest antioxidant potential. A bioassay-guided fractionation led to the isolation and characterization of seven compounds for the first time, namely, quercetin (1 ), 3-methoxy quercetin (2 ), kaempferol (3 ), 3-methoxy kaempferol (4 ), myricetin 3, 7, 3′-trimethyl ether (5 ), lupeol (6 ), and stigmasterol (7 ). Conclusion: Our results indicate that P. resinosa is a source for antimicrobial and cytotoxic compounds. However, further work is required to isolate other active principles and to determine the mechanism of action.